Retroperitoneal laparoscopic adrenalectomy: its role in the management of adrenal tumour and tertiary care centre experience - Singh Thakur, Avinash Pratap; Venugopal, G.; S., Darsan (International Journal of Research in Medical Sciences, 2020)
Background: Laparoscopic adrenalectomy for adrenal tumour has gained increased popularity worldwide. To decrease the complications of commonly used transperitoneal approach, by not entering into peritoneal cavity the retroperitoneal laparoscopic adrenalectomy (RLA) has developed. It has several advantages over the transperitoneal approach and associated with reduced morbidity and excellent outcome. The objective of this study was to report our experience with RLA for treatment of adrenal tumour. Methods: The study was done from August 2014 and December 2017, data of 44 patients who underwent RLA for adrenal tumour in the institute were retrospectively reviewed. Patient’s demographical, clinical, diagnostic and procedural data were recorded. All patients were assessed by history, physical examinations, laboratory values with biochemical marker test and imaging by computed tomography/magnetic resonance imaging. Treatment outcome was assessed in terms of operative time, haemoglobin drop, conversion rate, hospital stay and complications. Results: In 44 adrenalectomy, 24 men and 20 women, with a mean age of 47.0±8.9 years were enrolled. Mean body mass index was 23.5±2.2 kg/m2. Right adrenal tumour was seen in 26 cases and left in 18 cases. Mean adrenal mass size was 2.6±0.85 cm. Mean operative time was 109.1±21.16 minutes, mean haemoglobin drop was 0.47±0.26 gram/L. Conversion to open surgery was necessary in 2 patients. Mean postoperative hospital stay was 4.0±0.91 days. Recovery time mean value was 12.18±1.7 days postoperatively. In final histopathology result adenoma was most prevalent (25 cases) and myelolipoma was least (1 case). Conclusions: RLA appears to be safe and effective alternative to transperitoneal adrenalectomy for moderate size adrenal tumour in particular less than 6 cm. It is associated with less blood loss, shorter hospitalization, low conversion rate, fewer complications and early recovery. RLA offers an alternative method for treating adrenal tumour with improved surgical outcomes.